2021
DOI: 10.1007/s00167-021-06730-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging does not reliably detect Kaplan fiber injury in the setting of anterior cruciate ligament tear

Abstract: Purpose There has been a continued efort to better understand the role Kaplan iber injury plays in persistent instability following ACL tears. However, the prevalence of these injuries remains poorly understood. Therefore, the purpose of this study was to deine the prevalence of Kaplan iber injury in the setting of complete anterior cruciate ligament tear using a commonly used grading system for assessing ligament injuries. The inter-rater reliability of this commonly used grading system and the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Several very recent papers tried to identify the incidence of Kaplan fiber injury in the context of ACL rupture. To this end, Berthold et al [ 7 ], through a well-performed Magnetic Resonance study with three independent reviewers, retrospectively identified a relevant number of patients with concomitant injury to the Kaplan fibers, confirming the results of similar studies [ 8 , 9 ]. Other authors have tried to correlate Kaplan fiber injury with laxity or concomitant injuries, with contrasting and inconclusive results [ 8 , 10 ].…”
mentioning
confidence: 59%
“…Several very recent papers tried to identify the incidence of Kaplan fiber injury in the context of ACL rupture. To this end, Berthold et al [ 7 ], through a well-performed Magnetic Resonance study with three independent reviewers, retrospectively identified a relevant number of patients with concomitant injury to the Kaplan fibers, confirming the results of similar studies [ 8 , 9 ]. Other authors have tried to correlate Kaplan fiber injury with laxity or concomitant injuries, with contrasting and inconclusive results [ 8 , 10 ].…”
mentioning
confidence: 59%
“…The prevalence of KF injury in acute ACL tear among adults has been reported to be between 23% and 71% using various KF injury criteria. 4 , 5 , 17 , 18 , 22 The published criteria of Batty et al 4 reported an acute KF injury rate of 23.7%. The present study found a KF injury rate of 11.1% (95% CI, 1.9%-20.2%), which suggests that KF injury may be less common in the skeletally immature patient population or that the Batty et al 4 KF diagnostic criteria are less reliable in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…The 37.7% incidence of KF injury found among the present cohort using the Van Dyck et al 22 grading scheme is similar to previous studies looking at an adult population, with reported rates of 33% to 39%. 17 , 22 The observed difference in prevalence between the 2 injury criteria can be explained by the fact that isolated periligamentous edema is not considered a KF injury in the Batty scheme. In addition, the Batty group showed that the incidence of KF injury detected on MRI scans outside of the first 90 days from the date of injury was roughly a quarter of the initial rate at 6.4%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T he Society of Military Orthopaedic Surgeons, founded in 1958 on Governor's Island, NY, USA, has long focused on the musculoskeletal care of the combat-wounded warrior [11]. The unique demands of combat medicine have driven the need for ingenious solutions to difficult problems, including prolonged field care, airborne evacuation, and volumetric muscle loss with subsequent rehabilitation challenges in limb salvage [9,[15][16]. Upon its recognition and incorporation into the The 2021 SOMOS Annual Meeting was no exception, featuring the impressive efforts of the SOMOS membership to include our international colleagues.…”
mentioning
confidence: 99%